Controlled Synthesis of Pt Doped SnO2 Mesoporous Hollow Nanospheres for Highly Selective and Rapidly Detection of 3-Hydroxy-2-Butanone Biomarker - Cai, Haijie; Liu, Haiquan; Ni, Tianjun; Pan, Yingjie; Zhao, Yong; Zhu, Yongheng (Frontiers in Chemistry, 2019)
Listeria monocytogenes has been recognized as one of the extremely hazardous and potentially life-threatening food-borne pathogens, its real-time monitoring is of great importance to human health. Herein, a simple and effective method based on platinum sensitized tin dioxide semiconductor gas sensors has been proposed for selective and rapid detection of Listeria monocytogenes. Pt doped SnO2 nanospheres with particular mesoporous hollow structure have been synthesized successfully through a robust and template-free approach and used for the detection of 3-hydroxy-2-butanone biomarker of Listeria monocytogenes. The steady crystal structure, unique micromorphology, good monodispersit and large specific surface area of the obtained materials have been confirmed by X-ray diffraction (XRD), Raman spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS), Brunauer-Emmett-Teller (BET) and Photoluminescence spectra (PL). Pt doped SnO2 mesoporous hollow nanosphere sensors reach the maximum response of 3-hydroxy-2-butanone at 250 °C. Remarkably, sensors based on SnO2 mesoporous hollow nanospheres with 0.16 wt% Pt dopant exhibit excellent sensitivity (Rair/Rgas=48.69) and short response/recovery time (11/20 s, respectively) to 10 ppm 3-hydroxy-2-butanone at the optimum working temperature. Moreover, 0.16 wt% Pt doped SnO2 gas sensors also present particularly low limit of detection (LOD=0.5 ppm), superb long-term stability and prominent selectivity to 3-hydroxy-2-butanone. Such a gas sensor with high sensing performance foresees its tremendous application prospects for accurate and efficient detection of foodborne pathogens for the food security and public health.